Integrating Cryotherapy into Dental Practice: A New Frontier in Patient Care - Dr. Divleen Kaur, Dr. Aditi Pustake, Dr. Krishna Dave, Dr. Sheikh Mahfuza, Dr. Ami Shukla5, Dr. Puneet Prasher (South Eastern European Journal of Public Health, 2025)
In the realm of dentistry, cryotherapy stands as a powerful cold therapeutic technique, revolutionizing various sectors such as postoperative care, edema reduction, and pain management. Its applications now extend beyond these areas to encompass oral cancer treatment, implantology, endodontics, and oral lesion management. As a cost-effective and minimally invasive solution, cryotherapy accelerates patient recovery by inducing vasoconstriction and modulating inflammatory responses. However, despite its advantages, challenges such as precise temperature control and other contradictory issues persist. To refine its procedures, enhance its effectiveness, and unlock its full potential in dentistry, more in-depth research is essential.